High‐Performance Thick‐Film All‐Polymer Solar Cells Created Via Ternary Blending of a Novel Wide‐Bandgap Electron‐Donating Copolymer. Issue 14 (13th February 2018) - Fan, Baobing; Zhu, Peng; Xin, Jingming; Li, Ning; Ying, Lei; Zhong, Wenkai; Li, Zhenye; Ma, Wei; Huang, Fei; Cao, Yong
Abstract: A novel wide‐bandgap electron‐donating copolymer containing an electron‐deficient, difluorobenzotriazole building block with a siloxane‐terminated side chain is developed. The resulting polymer, poly(4, 8‐bis(4, 5‐dihexylthiophen‐2‐yl)benzo[1, 2‐b:4, 5‐b′]dithiophene‐co‐4, 7‐di(thiophen‐2‐yl)‐5, 6‐difluoro‐2‐(6‐(1, 1, 1, 3, 5, 5, 5‐heptamethyltri‐siloxan‐3‐yl)hexyl)‐2H‐benzo[d][1, 2, 3]triazole (PBTA‐Si), is used to successfully fabricate high‐performance, ternary, all‐polymer solar cells (all‐PSCs) insensitive to the active layer thickness. An impressively high fill factor of ≈76% is achieved with various ternary‐blending ratios. The optimized all‐PSCs attain a power conversion efficiency (PCE) of 9.17% with an active layer thickness of 350 nm and maintain a PCE over 8% for thicknesses over 400 nm, which is the highest reported efficiency for thick all‐PSCs. These results can be attributed to efficient charge transfer, additional energy transfer, high and balanced charge transport, and weak recombination behavior in the photoactive layer. Moreover, the photoactive layers of the ternary all‐PSCs are processed in a nonhalogenated solvent, 2‐methyltetrahydrofuran, which greatly improves their compatibility with large‐scale manufacturing. Abstract : A novel electron‐donating copolymer, PBTA‐Si, containing a benzotriazole building block with a siloxane‐functionalized side chain, is developed and used to fabricate thick‐film all‐polymer solar cells (all‐PSC). By means of ternary blending, the all‐PSCs attain a power conversion efficiency of 9.17% with a 350 nm thick active layer and 8.34% with a thickness of 420 nm.